Analysis of the Role of Digital Transformation, Infrastructure Availability, and Human Resource Competence on the Operational Performance of the Logistics Industry in Jakarta - Renalwin Sitorus; Eka Immamah; Aan Adiazmil (West Science Interdisciplinary Studies, 2026)
The rapid development of the logistics industry in Jakarta has increased the need for organizations to improve operational performance through digitalization, infrastructure readiness, and workforce capability. This study aims to analyze the role of digital transformation, infrastructure availability, and human resource competence on the operational performance of logistics companies in Jakarta. A quantitative research approach was applied using survey data collected from 150 respondents through a structured questionnaire measured with a five-point Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability testing, classical assumption tests, multiple linear regression, t-tests, and F-tests. The results indicate that digital transformation has the strongest positive and significant effect on operational performance, followed by human resource competence and infrastructure availability. Simultaneously, the three variables significantly influence operational performance with an R² value of 0.623, indicating that 62.3% of performance variation can be explained by the research model. The findings suggest that integrating digital technologies with adequate infrastructure and competent human resources is essential for improving efficiency, service reliability, and competitiveness in the logistics sector. This study contributes to the literature by providing empirical evidence on the combined role of technological, infrastructural, and human capital factors in enhancing operational performance within a metropolitan logistics environment.